Novel hydrothermal method for effective doping of N and F into nano Titania for both, energy and environmental applications. (February 2016) - Jyothi, M.S.; D'Souza Laveena, P.; Shwetharani, R.; Balakrishna, Geetha R.
Graphical abstract: Highlights: Novel method to synthesize N, F doped TiO2 via hydrothermal method is discussed. Change in bandgap of TiO2 upon doping makes a photocatalyst visible active. 94% of degradation of EtBr was achieved within a less time of 90 min. The doped titania also showed good efficiency as photo anodic material for solar cell. Abstract: A novel and an efficient hydrothermal method for the preparation of an effective doped titania photocatalyst is reported. The crystal phase, binding energy, elemental composition, morphology, optical and electronic structure analyses were done by various techniques. The doped titania proved as an efficient electrode material and photocatalyst for solar cells and water treatment respectively. The photocatalyst is able to degrade the most potent mutagen ethidium bromide under sunlight with an enhancement of 1.6 times over its undoped analogue. As photo-anode material, showed an improved open circuit potential and fill factor. The created electron states in the doped sample act as charge carrier traps suppressing recombination which later detraps the same to the surface of the catalyst causing enhanced interfacial charge transfer. Surface acidity caused by F induction and lowered band gap energy that can respond to visible light facilitates improved energy harvesting and energy transfer leading to better photo activity.